Food and its cultural dimensions: An integrative literature review - Otálvaro, Ángela; Vásquez, Olga; Murcia, Diana Marcela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Introduction: The relationship between food and culture is broad, therefore, the research agenda on the subject is exposed, through the review of indexed articles published between 2016 and 2022. Objective: to synthesize the academic production of the last years taking into account the key themes, the countries of production and the theoretical-methodological currents used in the research designs. Methodology: Integrative documentary review. Conclusions: The literature found is presented through six major thematic axes: food and medicine, identity and nation, transmission of knowledge, G-local relations and social dimensions.